Efficient Cu-catalyzed base-free C–S coupling under conventional and microwave heating. A simple access to S-heterocycles and sulfides - Soria Castro, Silvia Mercedes (2013)
S-aryl thioacetates can be prepared by reaction of inexpensive potassium thioacetate with both electron-rich and electron-poor aryl iodides under a base-free copper/ligand catalytic system. CuI as copper source affords S-aryl thioacetates in good to excellent yields, by using 1,10-phenanthroline as a ligand in toluene at 100 °C after 24 h. Under microwave irradiation the time was drastically reduced to 2 h. Both procedures are simple and involve a low-cost catalytic system. This methodology was also applied to the “one-pot” synthesis of target heterocycles, such as 3H-benzo[c][1,2]dithiol-3-one and 2-methylbenzothiazole, alkyl aryl sulfides, diaryl disulfides and asymmetric diaryl sulfides in good yields.